Commodity shocks, factor intensity and conflicts in Africa - Marcelo Gantier Mita (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2020)
Natural resources are often related to conflicts. The Dal B'o & Dal B'o (2011) theory states that income shocks affect capital- and labor-intensive sectors differently. Using sub-national cells covering the African continent for 1997-2010, I find that conflicts react differently to positive commodity price shocks depending on their factor intensity. The results show that a positive shock in the capital-intensive mining sector increases conflict likelihood, whereas a positive shock in the labor-intensive agricultural sector reduces it. These impacts are higher for sub-Saharan Africa. When testing heterogeneous effects for the degree of commodity appropriability, historical African-specific factors, and quality of institutions, I find that easily taxed crops behave differently to an increase in international crop prices. In the same vein, I find that neither historical African-specific factors nor the quality of institutions seem to induce differential responses in conflicts to commodity price shocks.
Keywords: O13; Q32; Q34; D74; 330; Natural Resources; Conflicts; Commodity Shocks